Rapid pickling method of salted duck egg using alternating hot and cool conditions and ultrasonic treatment - Ning Wang; Yizhi Ling; Zihan Li; Xueqin Gao; Xiaolin Jin; Yinchen Hou; Jian Zou (Food Science of Animal Products)
Salted duck egg (SDE) is a traditional Chinese food. The traditional curing method needs a long period. To shorten the pickling process, ultrasonic power, ultrasonic time, and ultrasonic alternating temperature were employed as the single factor to produce SDE. The salt content of SDE white and yolk and texture, ultrasonic apparent oil yield rate of SDE yolk were selected as test index. The results showed that all three factors affected the quality of SDE to different degrees. The trend related to the change of salt content was in line with that of the apparent oil yield rate. The higher product quality and shorter pickling process were observed when treated with ultrasonic power of 240 W, ultrasonic time of 90 min, and heating/cooling time for 14 h/10 h. Suitable levels for three factors were set for the orthogonal experiment according to the results of the single-factor experiment. The results showed that the optimal experiment level was 240 W of ultrasonic treatment for 90 min at a time ratio of 14 h/10 h, shortening the pickling time to 18 d. Thus, this work established a faster physical pickling method for SDE. Ultrasonic treatment could improve the quality of products, and alternating temperature could provide a temperature pump to accelerate the pickling speed, which could be considered to assist the low-salt curing process.